Japanese approaches to multi-script database provision - Wells, David (East Asian Library Resources Group of Australia, 1998)
This paper is based on research carried out in Japan during 1996 with the support of a Travelling Scholarship from the Victorian Association for Library Automation. I was able to visit approximately thirty libraries and information services and to conduct detailed interviews with staff in about half of these. I chose institutions known to have large multi-lingual collections in various parts of Japan. These are drawn mostly from the university and public library sector, though they also include special libraries and centralised information agencies. The purpose of my research was to investigate the provision in Japan of multi-language and multi-script bibliographic databases, that is systems which combine records in different languages and scripts within the same database. This paper discusses practical and theoretical issues in multi-script database creation, describes sample implementations and examines prospects for future development.